High prevalence of developmental delay among children under three years of age in poverty-stricken areas of China. Issue 12 (December 2015) - Wei, Q.W.; Zhang, J.X.; Scherpbier, R.W.; Zhao, C.X.; Luo, S.S.; Wang, X.L.; Guo, S.F.
Abstract: Objectives: Poverty and its associated factors put children at risk for developmental delay. The aim of this study was to describe the neurodevelopment of children under three years of age in poverty-stricken areas of China and explore possible associated factors. Study design: A cross-sectional survey was conducted among 2837 children aged 1–35 months in poverty-stricken areas of China. Methods: Characteristics of the child, caregiver, and family were collected through face-to-face caregiver interviews. Developmental delay was explored with the five-domain, structured, parent-completed Ages and Stages Questionnaire. The Zung Self-rating Depression Scale was used to assess depressive symptoms of the caregivers. The Chi-squared test and multivariate logistic regression analyses were used to explore associated factors. Results: Of the children, 39.7% (95% confidence interval, 37.9–41.5) had developmental delay in at least one of the five domains. For the domains of communication, gross motor, fine motor, problem solving, and personal-social skills, the prevalence was 11.5%, 18.5%, 21.4%, 18.4%, and 17.9%, respectively. Significant predictors of increased odds of developmental delay included the child having no toys (odds ratio [OR] = 2.31), the caregiver having depression (OR = 2.24), insufficient learning activities (OR = 1.65), and more children in the family (OR = 1.16). Conclusions: The high prevalence of developmental delay in children younger than three years in poverty-stricken areas of China and the presence of risk factors for developmental delay such as inadequate learning resources and activities in the home, caregiver depression, and low family income highlight the need for early identification and interventions. Highlights: The prevalence of developmental delay was high among children under three years of age. A large number of primary caregivers had depression symptoms. Children living in poverty need early identification and interventions.